(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article examines the significance of the patriotic qualities of Jaloliddin Manguberdi and their role in the moral and civic education of youth. It analyzes how his courage, leadership, loyalty to the homeland, and resistance against foreign invasion can serve as an educational model in shaping patriotism among younger generations. The study emphasizes the importance of integrating historical examples of national heroes into modern educational practices to strengthen national identity, responsibility, and ethical values in youth development.